K.H. Raden Muhammad Adnan (1889-1969 M): Ulama dan Pejuang di Bidang Pendidikan, Politik, dan Agama dari Kauman Surakarta - Islah Gusmian (Jurnal Lektur Keagamaan, 2017)
This article describes the life history of K.H. R. Muhammad Adnan and the roles he plays in education, social, political, and religious fields. This study is written with a social history approach as well as diachronic and synchronic analysis. The concept of elite developed by Weber, in this article is also used to see the existence of Kiai Adnan as a figure born among the elite and raised in the tradition of pesantren education. His existence has a strong influence on his functional orientation, both social, political, and religious functions. In the field of religion, from the era of physical revolution to independence, Kiai Adnan has played an important role, namely to develop religious education by establishing various schools and boarding schools. In the field of socio-politics, Kiai Adnan appear as a likeable figure and can be accepted by many circles, and made politics as a means of devotion to the nation. The characteristics and his father's upbringing have made him a transformed figure, and throughout his life he has devoted himself to the progress of the nation and the glory of his religion.Keywords: Kiai, Surakarta, Politics, Islam, IndonesiaArtikel ini menguraikan tentang sejarah hidup K.H. R. Muhammad Adnan dan peran-peran yang dimainkannya di bidang pendidikan, sosial, politik, dan keagamaan. Topik ini ditulis dengan pendekatan sejarah sosial serta analisis diakronis dan analisis sinkronis. Konsep elite yang dikembangkan Weber, dalam artikel ini juga dipakai untuk melihat eksistensi Kiai Adnan sebagai sosok yang lahir di kalangan elite dan dibesarkan dalam tradisi pendidikan pesantren. Eksistensinya ini mempunyai pengaruh terhadap orientasi fungsionalnya, baik fungsi sosial, politik, dan keagamaan. Di bidang agama, sejak era revolusi fisik hingga kemerdekaan, Kiai Adnan telah memainkan peran penting, yaitu mengembangkan dunia pendidikan agama dengan mendirikan berbagai sekolah maupun pesantren. Di bidang sosial-politik, Kiai Adnan tampil sebagai tokoh yang cair dan bisa diterima oleh semua kalangan, serta menjadikan politik sebagai sarana pengabdian kepada bangsanya. Karekter dan didikan ayahnya telah menjadikan dirinya sebagai sosok yang telah bertransformasi menjadi dirinya sendiri, dan di sepanjang hidupnya ia mengabdikan dirinya untuk kemajuan bangsa dan kemuliaan agamanya.Kata kunci: kiai, surakarta, politik, Islam, Indonesia